2003
DOI: 10.1177/0193945903025004002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Perceived Health of HIV Seropositive Men

Abstract: The purpose of this study was to examine the relationships between hope, social support, uncertainty in illness, and spirituality and their effect on the perceived health of HIV seropositive men. A prospective design was used to test a causal model on a sample of 125 HIV seropositive men recruited from urban HIV/AIDS outpatient clinics. A goodness of fit index of .90 and a comparative fit index of .79 indicated minimal fit of the theorized model with the data. Findings revealed significant, positive paths from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This finding is collaborated by similar findings in which hope was found to be an important internal resource for the increased functioning of PLWHA [11,25]. The greatest impact of hope was on environmental functioning and the lowest was on global functioning.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This finding is collaborated by similar findings in which hope was found to be an important internal resource for the increased functioning of PLWHA [11,25]. The greatest impact of hope was on environmental functioning and the lowest was on global functioning.…”
Section: Discussionsupporting
confidence: 69%
“…Specific ways of being in relationships with others include dealing with one's family, renegotiating the friendship group, helping others with HIV and developing a relationship with a higher power, and in this case, social support act as the functional component of relationships, such as emotional and tangible assistance [5]. A study on HIV infected terminally ill persons indicates that there were significant differences in the level of hope according to diagnosis [26], and hope can help PLWHA to deal with the HIV diagnosis and acts as an internal resource for helping individuals living with HIV to experience increased well-being [25].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Such factors can be modified for those aging with this disease. In particular, good health practices (Heinrich, 2003) and reducing depression (Honn & Bornstein, 2002) are recommended. In particular, adherence to HAART is not only important for immune function, it is important for cognitive maintenance.…”
Section: Assessment Prevention and Interventionmentioning
confidence: 99%
“…International research has found that social support can reduce feelings of social isolation, prevent mental illness, slow disease progression, promote treatment compliance, enhance coping strategies, and improve quality of life [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Only a few quantitative social support studies of PLWHA have been conducted in China, most using the Social Support Rating Scale (SSRS), which was developed by Xiao for non-PLWHA Chinese in 1986 [26,27].…”
Section: Introductionmentioning
confidence: 99%